2016
DOI: 10.1134/s2079970516030035
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diversification in the regional economy (Case study of subjects of the Siberian Federal District)

Abstract: The article deals with the problem of assessing economic diversification at the level of individual federal subjects. Diversification is one of the strategic goals for development of Siberia. Assessing the progress in furthering this goal requires its consideration at the level of measurable indicators. In world practice, measurement and evaluation of the level of diversification of the regional economy are based on a variety of indicators reflecting individual characteristics of diversification processes. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Besides, they support results earlier obtained by (Ankudinov et al, 2012) and (Mikheeva, 2013) who detected positive influence of diversification of economy on main indicators of regional economies including growth and employment. But they apparently contradict to (Kravchenko, 2016) who used other indicators and measured diversification by means of Herfindahl-Hirschman index which suggests uniform distribution as benchmark, unlike the overall structure of Russian economy.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Besides, they support results earlier obtained by (Ankudinov et al, 2012) and (Mikheeva, 2013) who detected positive influence of diversification of economy on main indicators of regional economies including growth and employment. But they apparently contradict to (Kravchenko, 2016) who used other indicators and measured diversification by means of Herfindahl-Hirschman index which suggests uniform distribution as benchmark, unlike the overall structure of Russian economy.…”
Section: Discussionmentioning
confidence: 72%
“…Another study of Russian regions conducted by (Mikheeva, 2013) for 2000 -2011 established that more diversified regional economies in Russia on average demonstrate more stable economic growth, whereas more specialized regions show the higher rates of it. On the contrary, (Kravchenko, 2016) in the study of the regions of Siberian Federal District revealed strong negative influence of the share of employed persons in manufacturing activity and the level of export specialization on the level of unemployment, concluding that there is no evidence of positive impact of economic diversity on its stability.…”
Section: Introductionmentioning
confidence: 89%
“…В исследованиях российских ученых также предложены подходы к оценке уровня диверсификации экономики региона 1 [16][17]. Так, А. А. Кофанов [18] применяет структурный коэффициент вклада добавленной стоимости конкретного вида экономической деятельности в валовый региональный продукт, который определяется как частное от деления доли добавленной стоимости в валовом региональном продукте конкретного региона (dr) на удельный вес добавленной стоимости этого вида в целом по стране (drf):…”
Section: теоретическая база исследованияunclassified